ANALYSIS OF THE IMPACT OF COVID-19 ON GROUP C EXCAVATION TAX REVENUE - Farafika, Nur; Damayanti, Ratna Ayu; Usman, Asri; Zalshabila, Shavira (Contemporary Journal on Business and Accounting, 2023)
Purpose – This study aims to determine the impact of Covid-19 on tax revenues from taking class C minerals in Barru Regency Design/methodology/approach – The analytical method used is descriptive analysis by calculating the growth rate and contribution formula Findings – The results of this study are that Covid-19 affects the determination of target setting, revenue realization, growth rate and tax contribution for taking group C minerals in Barru Regency Originality – Sources of data used in this study are secondary data obtained through documentation and library research Keywords: Covid-19, Tax Revenue, Tax on Extraction of Minerals Group C Paper Type Research Result